Development of Simple NFT Marketplace Using Free Coding from GitHub - Tung, Siau; Chang, Amelia (International Journal of Art, Design, and Metaverse, 2023)
This research project explores the development of a Non-Fungible Token (NFT) marketplace by leveraging existing coding methods available on GitHub. The study aims to create a simplified NFT marketplace with a focus on practical implementation. By utilizing open-source resources and repositories from GitHub, the project seeks to provide insights into the construction of a basic NFT marketplace, highlighting the fundamental coding techniques and considerations involved. The research findings offer a foundational understanding of building a straightforward NFT marketplace, serving as a valuable starting point for developers and enthusiasts looking to enter the NFT space. While the scope of this project is limited to a simple NFT marketplace, it lays the groundwork for future exploration and expansion into more complex and feature-rich NFT trading platforms.